2020
DOI: 10.1002/adfm.202001294
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Crystal Formation in Ruddlesden–Popper Sn‐Based Perovskites

Abstract: Knowledge of the mechanism of formation, orientation, and location of phases inside thin perovskite films is essential to optimize their optoelectronic properties. Among the most promising, low toxicity, lead-free perovskites, the tin-based ones are receiving much attention. Here, an extensive in situ and ex situ structural study is performed on the mechanism of crystallization from solution of 3D formamidinium tin iodide (FASnI 3 ), 2D phenylethylammonium tin iodide (PEA 2 SnI 4 ), and hybrid PEA 2 FA n−1 Sn … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
116
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 56 publications
(78 reference statements)
3
116
0
Order By: Relevance
“…The evaporation of the solvent during the annealing process causes the intermediate to slowly release PbI 2 to form the perovskite phase, and the intermediate acts as a framework to facilitate the construction of perovskite QW ( Figure 4 a). In the second stage, the crystallization of 2D perovskite precursor has priority over the formation of a 3D‐like perovskite phase at the gas‐liquid interface, [ 100 ] which is a critical step. Ensure the process is not disturbed is a necessary condition for obtaining the preferred orientation.…”
Section: Crystallization Kineticsmentioning
confidence: 99%
“…The evaporation of the solvent during the annealing process causes the intermediate to slowly release PbI 2 to form the perovskite phase, and the intermediate acts as a framework to facilitate the construction of perovskite QW ( Figure 4 a). In the second stage, the crystallization of 2D perovskite precursor has priority over the formation of a 3D‐like perovskite phase at the gas‐liquid interface, [ 100 ] which is a critical step. Ensure the process is not disturbed is a necessary condition for obtaining the preferred orientation.…”
Section: Crystallization Kineticsmentioning
confidence: 99%
“…The high crystallinity and orientational order observed in 2D/3D film are associated with the changes in the crystallization process, in which 2D tin perovskite promotes the surface crystallization of the 3D tin perovskite. [ 32 ] Figure S3 (Supporting Information) shows the atomic force microscopy (AFM) images of the two films. The pure 3D film exhibits large grains with sharp grain boundaries, while the 2D/3D film shows fused grain boundaries.…”
Section: Resultsmentioning
confidence: 99%
“…It has been concluded that Sn‐based perovskites tend to form without through a direct conversion of a disordered precursor phase without the formation of ordered solvated intermediates and the postannealing process. [ 102 ]…”
Section: Fundamental Understanding Of Rp Perovskites Film In Pscsmentioning
confidence: 99%